Solid-pseudopapillary neoplasia of the pancreas (analysis of three cases) - V. M. Durleshter; S. R. Heinrich; D. S. Kirakosyan (Вестник хирургии имени И.И. Грекова)
The objective was to improve the early diagnosis efficiency of large pseudopapillary tumor of pancreas through the demonstration and analysis of three clinical cases.Methods and materials. In this work, the observation period was two years, in which three cases were diagnosed and treated a large number of pseudopapillary tumors.Results. With sufficient information on the characteristics of this disease, over the past 5 years we have had an opportunity to determine a diagnosis in two patients before the tissue examination.Conclusion. The age of patients, clinical manifestations, tumor size and the age of tumor patients are not reliable criteria for predicting the possibility of malignant tumors. Performing the operation in compliance with the principles of radicalism provide the best opportunity for recovery and reduces the early incidence of postoperative complications.